STUDY OF THE INFLUENCE OF IMPROVED POWER SUPPLY SYSTEM, BY THE APPLICATION OF GAS INTAKE DEVICE, ON THE GAS DIESEL ENGINE INDICES - Poliakov, Andriy; Maryanko, Bogdan (Scientific Works of Vinnytsia National Technical University, 2015)
The paper gives data on the efficiency of the gas intake device application in gas-diesel engines. Mathematical calculations of the cycles are presented for diesel and gas-diesel engines with gas intake device and without it. REFERENCES 1. Авдеев А. В. Контроль сжигания газообразного топлива / Авдеев А. В. – М.: Энергия, 1975. – 254 с. 2. ГОСТ 14846-81 (СТ СЭВ 765-77). Двигатели автомобильные. Методы стендовых испытаний. – [Чинний від 1982-01-01]. – М. : Изд-во стандартов, 1981. – 55 с. 3. Математическая модель системы “Водитель – автомобиль с газодизелем – дорога – окружающая среда” / К. Е. Долганов, А. П. Поляков, З. И. Краснокутская [та ін.] // Укр. трансп. ун–т. – Киев. – 1996. –39 с. 4. Поляков А. П. Експериментальні дослідження дозатора газу / А. П. Поляков, М. М. Мартиненко // Збірник наукових праць ЦНДІ ОВТ ЗСУ. – 2002. – Випуск 11. – С. 187 – 191.